A general scheme for spectral efficiency evaluation of direct-sequence spread-spectrum systems. - Bystrom, M. (IEEE Transactions on communications)
Typically, spectral efficiency, the throughput in bits/second/hertz, has been evaluated for fixed values of the bit error probability. We introduce a cutoff-rate-based approach to evaluation of the spectral efficiency of direct-sequence spread-spectrum schemes so that the results are independent of specific bit error rates or channel codes. Results are shown for M-ary phase-shift keyed modulation on the slow-fading Rician channel